An Unusual Presentation of Right Atrial Myxoma: A Case Report - Debmalya Saha; Lakshmi Sinha; Satyajit Samal; Parag Sharma; Sayyed Ehtesham Hussain Naqvi; Muhammad Abid Geelani (Oman Medical Journal, 2023)
A right atrial myxoma extending to the inferior vena cava with associated right-to-left shunting leading to systemic desaturation is an exceedingly rare clinical entity. The number of cases reported in the literature to date is not more than five. This case study presents a 45-year-old female who was referred to our center with symptoms of breathlessness, easy fatigability, generalized weakness, and central cyanosis. On routine blood investigation, polycythemia was detected. On preoperative 2D-transthoracic echocardiography, the diagnosis of right atrial mass was confirmed but the reason for cyanosis was not revealed. A tumor thrombus in a branch of the right lower pulmonary artery with a small locoregional pulmonary infarct along with right atrial myxoma was reported in computed tomography angiography of the heart and great vessels. On-table transesophageal echocardiography showed patent foramen ovale (PFO) with right-to-left shunting because of raised right atrial pressure and dynamic obstruction of the tricuspid valve by the mass. The myxoma was resected completely via right atrial approach along with primary closure of PFO. Postoperative period was uneventful, and the patient was discharged on day seven. At three-month follow-up, the patient was doing well.